Identification of a rare GLI3 variant associated with unilateral thumb polydactyly - Ngoc, Nguyen Thy; Duc, Hoang Hai (Vietnam Journal of Biotechnology, 2024)
Polydactyly is a congenital anomaly marked by supernumerary digits, resulting in an excess number of fingers or toes. Numerous investigations have elucidated the critical role of genetic factors in determining the presence of non-syndromic polydactyly. Nevertheless, a comprehensive understanding of the underlying signaling pathway responsible for this disorder remains incomplete. In this study, we present a thorough analysis of a unique unilateral polydactyly phenotype in the thumb of a 6-year-old male proband, employing exome sequencing. The investigation revealed a rare heterozygous substitution variant (NM_000168.6:c.1384A>G; p.Lys462Glu) in the GLI3 gene, a critical factor associated with polydactyly. Sanger sequencing confirmed the paternal inheritance of this variant. Notably, the amino acid change demonstrated evolutionary conservation, emphasizing its potential functional significance. Our findings contribute novel insights into the genetic underpinnings of polydactyly, highlighting the significant role of GLI3 in limb development. This discovery expands our understanding of the broader implications of GLI3 mutations in congenital limb abnormalities, paving the way for further investigations in this field. From a genetic perspective, unraveling the intricacies of polydactyly at the molecular level opens avenues for comprehending the broader genetic landscape of limb malformations and their underlying mechanisms.